FACTORS OF DEVELOPMENT OF PROFESSIONAL COMPETENCE OF TEACHERS OF PROFESSIONAL EDUCATIONAL INSTITUTIONS IN THE FIELD OF DIGITAL PEDAGOGY - Shaxodjayev Maxmud Axmedovich (American Journals, 2023)
Digitization of modern society has a significant impact on education and requires teachers of professional educational institutions to develop new competencies in the field of digital pedagogy. This scientific article examines the factors affecting the development of professional competencies of professors and teachers in the field of digital pedagogy. Based on the study of literature and empirical research, the main factors such as the level of technological literacy, availability of educational resources, professional support and motivation of teachers, as well as organizational conditions for the development of digital pedagogy were determined. The article provides recommendations for vocational and professional educational institutions aimed at developing the professional qualifications of professors and teachers in the field of digital pedagogy.
Keywords: Digital pedagogy, professional education, digital competence, digital technology, technological literacy, educational resources, modern education, knowledge, skills, competence.